Vagão Sustentável: the environmental education and social actions during the Covid-19 pandemic (International Journal of Geoscience, Engineering and Technology, 2023)
Environmental education has been constantly discussed in our daily lives and is fundamental for the development of society. In view of this, the present article aims to present actions of environmental education and of a social nature of the extension project of the Federal University of the Jequitinhonha and Mucuri Valleys (UFVJM), entitled Sustainable Wagon: Environmental Education in Schools of Teófilo Otoni- MG and Public awareness. For the present work, a case study was carried out, where data were obtained directly from the project's social media, and recorded in its monthly reports, during the pandemic period. The analysis of information was carried out through descriptive research in a quali-quantitative approach of previously programmed actions. During the covid-19 pandemic, environmental education activities were carried out in the distance modality (online actions) and social actions that took place in accordance with the health protocols to combat covid-19.